Population level outcomes and cost‐effectiveness of hepatitis C treatment pre‐ vs postkidney transplantation. Issue 10 (30th August 2018) - Shelton, Brittany A.; Sawinski, Deirdre; Linas, Benjamin P.; Reese, Peter P.; Mustian, Margaux; Hungerpiller, Mitch; Reed, Rhiannon D.; MacLennan, Paul A.; Locke, Jayme E.
Abstract : Direct‐acting antivirals approved for use in patients with end‐stage renal disease (ESRD) now exist. HCV‐positive (HCV+) ESRD patients have the opportunity to decrease the waiting times for transplantation by accepting HCV‐infected kidneys. The optimal timing for HCV treatment (pre‐ vs posttransplant) among kidney transplant candidates is unknown. Monte Carlo microsimulation of 100 000 candidates was used to examine the cost‐effectiveness of HCV treatment pretransplant vs posttransplant by liver fibrosis stage and waiting time over a lifetime time horizon using 2 regimens approved for ESRD patients. Treatment pretransplant yielded higher quality‐adjusted life years (QALYs) compared with posttransplant treatment in all subgroups except those with Meta‐analysis of Histological Data in Viral Hepatitis stage F0 (pretransplant: 5.7 QALYs vs posttransplant: 5.8 QALYs). However, treatment posttransplant was cost‐saving due to decreased dialysis duration with the use of HCV‐infected kidneys (pretransplant: $735 700 vs posttransplant: $682 400). Using a willingness‐to‐pay threshold of $100 000, treatment pretransplant was not cost‐effective except for those with Meta‐analysis of Histological Data in Viral Hepatitis stage F3 whose fibrosis progression was halted. If HCV+ candidates had access to HCV‐infected donors and were transplanted ≥9 months sooner than HCV‐negative candidates, treatment pretransplant was no longer cost‐effective (incremental cost‐effectiveness ratio [ICER]: $107 100). In conclusion, optimal timing of treatment depends on fibrosis stage and access to HCV+ kidneys but generally favors posttransplant HCV eradication. Abstract : This study finds that optimal timing for HCV treatment is modified by liver fibrosis stage and local wait times, with posttransplant treatment favored for patients with minimal fibrosis and pretransplant treatment favored for those with advanced disease.